Integrative Approach to Predict Severity in Nonketotic Hyperglycinemia. Issue 2 (16th June 2022) - Hübschmann, Oya Kuseyri; Juliá‐Palacios, Natalia Alexandra; Olivella, Mireia; Guder, Philipp; Zafeiriou, Dimitrios I.; Horvath, Gabriella; Kulhánek, Jan; Pearson, Toni S.; Kuster, Alice; Cortès‐Saladelafont, Elisenda; Ibáñez, Salvador; García‐Jiménez, Maria Concepción; et al.
Abstract : Objective: Glycine encephalopathy, also known as nonketotic hyperglycinemia (NKH), is an inherited neurometabolic disorder with variable clinical course and severity, ranging from infantile epileptic encephalopathy to psychiatric disorders. A precise phenotypic characterization and an evaluation of predictive approaches are needed. Methods: Longitudinal clinical and biochemical data of 25 individuals with NKH from the patient registry of the International Working Group on Neurotransmitter Related Disorders were studied with in silico analyses, pathogenicity scores, and molecular modeling of GLDC and AMT variants. Results: Symptom onset ( p  < 0.01) and diagnosis occur earlier in life in severe NKH ( p  < 0.01). Presenting symptoms affect the age at diagnosis. Psychiatric problems occur predominantly in attenuated NKH. Onset age ≥ 3 months (66% specificity, 100% sensitivity, area under the curve [AUC] = 0.87) and cerebrospinal fluid (CSF)/plasma glycine ratio ≤ 0.09 (57% specificity, 100% sensitivity, AUC = 0.88) are sensitive indicators for attenuated NKH, whereas CSF glycine concentration ≥ 116.5μmol/l (100% specificity, 93% sensitivity, AUC = 0.97) and CSF/plasma glycine ratio ≥ 0.15 (100% specificity, 64% sensitivity, AUC = 0.88) are specific for severe forms. A ratio threshold of 0.128 discriminates the overlapping range. We present 10 new GLDC variants. Two mild variants resulted in attenuated, whereas 2 severe variants or 1 mild and 1 severe variant led to severe phenotype. Based on clinical, biochemical, and genetic parameters, we propose a severity prediction model. Interpretation: This study widens the phenotypic spectrum of attenuated NKH and expands the number of pathogenic variants. The multiparametric approach provides a promising tool to predict disease severity, helping to improve clinical management strategies. ANN NEUROL 2022;92:292–303